2022
DOI: 10.1017/s0007123422000527
|View full text |Cite
|
Sign up to set email alerts
|

Encouraged to Cheat? Federal Incentives and Career Concerns at the Sub-national Level as Determinants of Under-Reporting of COVID-19 Mortality in Russia

Abstract: This article investigates the determinants and consequences of manipulating COVID-19 statistics in an authoritarian federation using the Russian case. It abandons the interpretation of the authoritarian regime as a unitary actor and acknowledges the need to account for a complex interaction of various bureaucratic and political players to understand the spread and the logic of manipulation. Our estimation strategy takes advantage of a natural experiment where the onset of the pandemic adjourned the national re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 131 publications
0
9
0
Order By: Relevance
“…A significant contribution to this debate is by Neumayer and Plümper (2022) , who investigated the “mortality gap”–the variance between reported COVID-19 fatalities and excess mortality, a metric endorsed by the World Health Organization ( World Health Organization, 2023 ). Their findings underscored a more notable gap in authoritarian states, a theme further explored in subsequent studies ( Kofanov et al, 2023 ).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…A significant contribution to this debate is by Neumayer and Plümper (2022) , who investigated the “mortality gap”–the variance between reported COVID-19 fatalities and excess mortality, a metric endorsed by the World Health Organization ( World Health Organization, 2023 ). Their findings underscored a more notable gap in authoritarian states, a theme further explored in subsequent studies ( Kofanov et al, 2023 ).…”
Section: Introductionmentioning
confidence: 67%
“…Recent scholarly inquiries into the disparity between reported excess mortality and official COVID-19 mortality rates predominantly attribute this gap to authoritarian leaders’ manipulation of data ( Balashov et al, 2021 , Kilani, 2021 , Neumayer and Plümper, 2022 , Kofanov et al, 2023 ). This study posits that the legislative body is a pivotal factor in ensuring the accuracy of mortality data.…”
Section: Legislature’s Importance In Reporting Covid-19 Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…They all followed the order to conduct the June/July referendum on constitutional amendments in 2020, regardless of the COVID-19 situation in their region. A comparison of excess mortality and reported COVID ISSN 2562-8429 statistics indicated that many of them appear to have manipulated COVID-19 death statistics to ensure conformity to the narratives in state media (Busygina and Filippov 2021;Kofanov et al, 2022). The image presented of a unified power vertical without dissenters is combined with deliberate distortion of Russia's COVID-19 response, which is bound to have an effect on public opinion.…”
Section: The Political Context Of the Coronavirus Pandemic And Russia...mentioning
confidence: 99%
“…Countries reported the total number of COVID‐19 cases and fatalities in their areas to the WHO, and this data has been made available. The COVID‐19 indices that are reported, however, fluctuate with time and place and are influenced or underreported 1 by established biases 2 . Recent studies, 3–7 including those from the WHO, 8–10 have noted that the data given does not give a clear picture of the health burden attributed to COVID‐19 or the number of lives lost, both directly and indirectly, as a result of the pandemic.…”
Section: Introductionmentioning
confidence: 99%